2007
DOI: 10.1111/j.1365-2486.2007.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Will northern fish populations be in hot water because of climate change?

Abstract: Predicted increases in water temperature in response to climate change will have large implications for aquatic ecosystems, such as altering thermal habitat and potential range expansion of fish species. Warmwater fish species, such as smallmouth bass, Micropterus dolomieu, may have access to additional favourable thermal habitat under increased surface-water temperatures, thereby shifting the northern limit of the distribution of the species further north in Canada and potentially negatively impacting native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
224
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(236 citation statements)
references
References 43 publications
10
224
1
1
Order By: Relevance
“…3B). Note that our findings do not discount the previous findings that competitors may act to decouple lake trout from near-shore fish production (22), nor that the distribution of bass is restricted by climate (26). In fact, bass are more likely to be present on average in our warmer study lakes (F = 4.393, n = 54, P = 0.041).…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…3B). Note that our findings do not discount the previous findings that competitors may act to decouple lake trout from near-shore fish production (22), nor that the distribution of bass is restricted by climate (26). In fact, bass are more likely to be present on average in our warmer study lakes (F = 4.393, n = 54, P = 0.041).…”
Section: Resultscontrasting
confidence: 53%
“…Smallmouth bass (Microterus dolomieu) and walleye (Sanders vitreus) are apex predators that inhabit the near-shore zone in several lake trout lakes in our study area. Because these species are expected to benefit from warmer summer temperatures over the climate range of our study (26), they may be an indirect cause of the overall decoupling effect observed across the climate gradient. In contrast to the prediction that warmwater predators are the primary driver of decoupling across a warming climatic gradient, our analysis of lakes without bass and walleye shows a similar if not stronger relationship between warming and the decoupling of lake habitats (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, global climate change will probably cause warmer water temperatures in northern-latitude lakes. This may cause seasonally stressful conditions for coldwater-adapted fish species, but may provide suitable thermal conditions to allow non-native warmer fish species (as well as the other organisms) to thrive in these lakes (Sharma et al, 2007). From this point of view, the Lake LicheƄskie gives us a unique option to imagine the composition of future fish communities in the present coldwater lakes.…”
Section: Populationmentioning
confidence: 99%
“…In this study we used the July temperature and the water defi cit in late summer as surrogates for direct measurements of the temperature in inland water bodies. Earlier studies have found especially the July air temperature to be a good predictor of maximum surface-water temperatures (Mohseni et al 2003, Sharma et al 2007). Water defi cit in late summer summarises the interactions between temperature and precipitation and thus also has the potentiality to indicate landscapes where the water levels in many lakes can become low, and consequently growing conditions can become more readily overly warm for Elodea canadensis.…”
Section: Climate Datamentioning
confidence: 99%